Combination of contracts in Islamic finance - Shahrul Azman Abd. Razak (0000123519, 2016)
Since the emergence of the industry, various contracts have been used to develop Islamic financial products, which have been described by classical jurists in their writing over centuries. These contracts have been employed by contemporary Islamic finance practitioners in order to develop innovative Islamic financial products. Combination of contracts appeared to become one of the mechanisms for product development tools. This book is seen as one of the opportunity for practitioners in the industry to apply the concept judiciuosly in accordance to the Shariah requisites.